Enhancing Students’ Speaking Skills through English Area Program at Islamic Boarding Schools - Irawati, Luluk; Ferdiyanto, Feri; Islam , Raudhatul (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The need for English language proficiency is becoming increasingly important in global communication, and its significance is becoming increasingly evident in the world of education. This study will examine students’ perspectives and the benefits of implementing the English Area Program in enhancing speaking skills among students in Islamic boarding schools. A qualitative descriptive approach was employed, using observation, questionnaires, and documentation as data collection methods. The participants were students actively involved in the English Area Program at the Wali Songo Al-Adnani boarding school. We employed data analysis techniques such as data reduction, data presentation, data condensation, and conclusion drawing. The findings reveal that the majority of students held a positive perspective of the program, as it created a supportive English-speaking environment that encouraged them to actively use the language. The program effectively improved students’ confidence, fluency, vocabulary mastery, and pronunciation. Moreover, the collaborative and interactive learning atmosphere significantly contributed to the development of their speaking competence. In conclusion, the English Area Program is an effective strategy for English language learning in boarding school settings, as it provides consistent and authentic opportunities for language use. These findings are expected to serve as a reference for educational institutions in designing similar programs to support students’ speaking skill development.